Large Scale Application of Self-Healing Concrete: Design, Construction, and Testing - Davies, Robert; Teall, Oliver; Pilegis, Martins; Kanellopoulos, Antonios; Sharma, Trupti; Jefferson, Anthony; Gardner, Diane; Al-Tabbaa, Abir; Paine, Kevin; Lark, Robert (Frontiers in Materials, 2018)
Materials for Life (M4L) was a 3 year, EPSRC funded, research project carried out by the Universities of Cardiff, Bath and Cambridge to investigate the development of self-healing cementitious construction materials. This paper describes the UK’s first site trial of self-healing concrete, which was the culmination of that project. The trial comprised the in-situ construction of five concrete panels using a range of self-healing technologies within the site compound of the A465 Heads of the Valleys Highway upgrading project. Four self-healing techniques were used both individually and in combination with one another. They were: (i) the use of microcapsules developed by the University of Cambridge, in collaboration with industry, containing mineral healing agents, (ii) bacterial healing using the expertise developed at Bath University, (iii) the use of a shape memory polymer (SMP) based system for crack closure and (iv) the delivery of a mineral healing agent through a vascular flow network. Both of the latter, (iii) and (iv), were the product of research undertaken at Cardiff University. This paper describes the design, construction, testing and monitoring of these trial panels and presents the primary findings of the exercise. The challenges that had to be overcome to incorporate these self-healing techniques into full-scale structures on a live construction site are highlighted, the impact of the different techniques on the behaviour of the panels when subject to loading is presented and the ability of the techniques used to heal the cracks that were generated is discussed.